2019
DOI: 10.1002/smi.2872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chewing gum on stress, anxiety, depression, self‐focused attention, and academic success: A randomized controlled study

Abstract: Chewing gum is thought to increase focus via a reduction in stress and anxiety. Chewing gum contributes to success by improving short-term memory. This study was conducted to determine the effect of chewing gum on stress, anxiety, depression, self-focused attention, and exam success. A randomized controlled trial was conducted with a total of 100 students. In the long-term (19 days) and short-term (7 days) chewing gum groups, the pretest scores of depression, anxiety, and stress were significantly higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Five studies were conducted in the UK, two are in Austria, and one in Turkey. For gum chewing, the chewing gum group was given spearmint-flavored, sugar-free gum [ 9 , 11 , 20 ], one was given extra spearmint and gum base [ 16 ], one was given sugarless [ 10 ], or sugar-free gum [ 23 ], and unclear [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies were conducted in the UK, two are in Austria, and one in Turkey. For gum chewing, the chewing gum group was given spearmint-flavored, sugar-free gum [ 9 , 11 , 20 ], one was given extra spearmint and gum base [ 16 ], one was given sugarless [ 10 ], or sugar-free gum [ 23 ], and unclear [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest that chewing gum was a cost-effective and easy to implement a way to reduce stress and get more done [ 8 ]. Chewing gum also has been associated with reduced anxiety [ 9 ], and a recent report proved that long-term chewing gum was effective in reducing stress, anxiety, depression, and improving test scores in school nursing students [ 10 ]. Conversely, some studies showed chewing gum cannot reduce acute stress or anxiety [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This fits the results of Keys et al (1950), whereby increased chewing/gum consumption helped regulate the psychological effects of starvation (e.g., distress, anxiety, depression) and food cravings, as suggested by more recent literature (Hetherington & Boyland, 2007; Hetherington & Regan, 2011; Zibell & Madansky, 2009). Increased chewing is also related to decreased cortisol levels (Tahara et al, 2007; Tasaka et al, 2018), stress perception, and anxiety in healthy individuals (Gray et al, 2012; Yaman‐Sözbir, Ayaz‐Alkaya, & Bayrak‐Kahraman, 2019), suggesting a “relaxing” effect, as earlier evidenced (Hollingworth, 1939), and further confirmed (Nishigawa, Suzuki, & Matsuka, 2015; Tasaka et al, 2018) in research related to psychosocial stress (Gray et al, 2012; Sketchley‐Kaye, Jenks, Miles, & Johnson, 2011; Yaman‐Sözbir et al, 2019). Consequently, in the present study, we supposed a relationship between chewing and stress; whereby increased chewing might have acted as a stress regulatory mechanism, but not specific to P AN .…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe an improvement in the cognitive domains of attention and memory, the individual neurocognitive function tests, mood, or anxiety with chewing gum compared to no chewing. Previous studies investigating the effects of chewing on neurocognitive function, mood, and anxiety have reported mixed results with studies observing improvements ( 53), (54), studies observing no effects (55,56) and indeed studies observing negative effects on the ability to perform cognitive tasks (52). Additionally, previous studies investigating the effects of nitrate intake on measures of neurocognitive function report mixed results.…”
Section: Discussionmentioning
confidence: 99%